Non-physiological shear stress-induced blood damage in ventricular assist device - Zengsheng Chen; Anqiang Sun; Hongyu Wang; Yubo Fan; Xiaoyan Deng (Medicine in Novel Technology and Devices, 2019)
Ventricular assist devices (VADs) have been used for treating the end-stage heart failure (HF) patients in the past few decades, which had improved survival rates. In parallel, clinical applications of VADs are accompanied with endangered complications, such as thrombosis, bleeding and infection, which hamper the patient recovery. Non-physiological shear stress (NPSS) is inevitably created during VAD application. When HF patients implanted with VADs, this high level NPSS can induce damage on blood components including blood cells (red blood cells, platelets, leukocytes et al.) and protein (von Willebrand Factor(VWF)). The damage of these blood cells and proteins may lead to the dysfunction of coagulation and immune systems, contributing to complications in VAD patients. To understand how VADs-created NPSS induces blood damage, and find the link between NPSS-induced blood damage and VAD related complications would potentially help to guide the VAD optimization and to find the effect way for treating VAD associated complications. Here we provide a review to investigate what is currently known about NPSS-induced blood damage within VADs and how the NPSS-induced blood damage links to complications (thrombosis, bleeding and infection) in VAD patients.